Analysis of Government Policy on Financial Performance of Zimbabwe Motor Industry: case Study of Croco Motor - Chidakwa, Edwin (Midlands State University, 2017)
The aim of the research is to analyze the government policies on financial performance of Zimbabwe Motor industry. The literature on the research study constituted all the objectives of the research study and what other authors have said about the government policies on financial performance. Questionnaires were used as the main data collection instruments essential in the collection of data. Primary and Secondary sources were both used to obtain data. The targeted population size used in this research was 55 and the sample size was constituted by 33 respondents. The information obtained from the data collected was analyzed by making use of a spread sheet and it was presented by making use of simple tables and graphs. From the research, the research findings also show that the Zimbabwe importation policy on second hand vehicles imposed by government is responsible for the decrease in demand of new vehicles from local automobile dealers. High utility charges have been affecting greatly on the financial performance of the industry. The researcher has also discovered that the industry is so much in need of capital therefore the government can use its policies to encourage Foreign direct investment and this can also attract foreign investors to invest in automobile sector. The recommendation was that, Zimbabwe Motor industry should sell vehicle parts for gray imports as well as servicing grey imports so that they can improve their profitability. Croco Motors must try to collaborate with banks and financial institutions in making sure that the potential customers have access to vehicle loans despite the lack of collateral security.